Effects of Lipid Peroxidation, Thyroid Hormones, and Some Vitamins in Type 2 Diabetic Patients - AL-Fayyadh, Mohanad S. (Iraqi Journal of Science, 2022)
One of the most common forms of diabetes is Type-2 that occurs due to the failure of cells in recognizing and responding to insulin if not accurately treated. The aim of this work is to evaluate the relations of thyroid hormones, vitamins, and lipid peroxidation with the glycemic index in patients experiencing Type-2 diabetes. Some tests of biochemical parameters and vitamins were conducted on 35 patients experiencing Diabetes Mellitus (DM) and 35 healthy subjects. The results indicated the increase in the levels of MDA (3.86 ± 0.97 µmol/L), HbA1c (8.27 ± 1.66 %), FBS (198.34 ± 32.41 mg/dl) and TSH (5.67 ±0.34 mIU/L) in the blood of diabetic subjects in comparison to the controls at a P value lower than 0.05. These increases resulted in decreasing the levels of GSH (3.68 ± 1.21 µM/mL), T3 (0.91 ± 0.03 ng/ml), vitamin E (0.66 ± 0.15 mg/dl), T4 (3.67 ± 0.46 µg/dl), and vitamin D3 (16.78 ± 4.32 mg/L) in diabetic subjects at the same P value. The present study concludes that there is relationship between thyroid hormones and oxidative stress in type 2 diabetes mellitus. In addition, there is a negative correlation between the levels of vitamin E, D, and HbA1c. Therefore, diabetics should monitor their levels of thyroid hormones and vitamins E and D.